Speed performance of space vector pulse width modulation direct torque for five leg inverter served dual three-phase induction motor - N.M., Yaakop; Zulkifilie, Ibrahim; Md Hairul Nizam , Talib (2012)
Independent control of multi-machine with singleconverter systems is the motivation of this research study. As in the previous literature review, there is no report regarding speed control applying space vector pulse width modulation direct torque control (SVPWM-DTC) method for dual three-phase induction motor (IM) fed by a five leg inverter (FLI). Therefore, in this paper, a new and simple control method based on SVPWM-DTC for dual three-phase induction motors with only one drive of five-leg voltage source inverter is investigated. The method effectively allows independent control of two three-phase IMs. Simulations of different speed commands and variation of load condition tests have been performed. Future work is to do comparative study between vector controls (VC) versus DTC methods to the FLI performance.